A Study on Public Perceptions of Carbon Neutrality in China: has the Idea of ESG Been Encompassed? - Li, Rita Yi Man; Wang, Qianqian; Zeng, Liyun; Chen, Hong (Frontiers in Environmental Science, 2023)
China has pledged to become carbon neutral by 2060 and has employed a variety of strategies to minimize carbon emissions. As people’s support to achieve the carbon neutrality goal affects its success, this study reviewed the public’s perception of carbon neutrality via cluster analysis on microposts. The co-occurrence matrix showed 258 nodes and 3,212 ties in the carbon neutrality social network. The top five most prominent nodes were neutralized, energy, China, blue-green, and economy. The keyword like blue-green (means water and plant) illustrated the popular terminology used by mainland Weibo users and its essential role in carbon neutrality. The multidimensional scaling analysis found that there were 11 clusters in carbon neutrality. The results revealed that people’s concerns about carbon neutrality were mainly related to the environment (e.g. low carbon, sustainable, and wind power), social (e.g. country and poverty), and governance (responsibility, government report). Weibo users believed that achieving carbon-neutrality allows us to pursue a better life. Among the data collected, positive sentiment microposts (83.9%) were approximately eight times more than the negative ones (9.9%), and only 6.3% were neutral. The results indicated that most Weibo users were opitimistic on carbon neutrality.